Preparation and reverse recycling logistics of a new type of nano-filled antibacterial layer packaging film for dairy products - Li, Quan; Zhou, Xiaorong; Wu, Hong (Frontiers in Chemistry, 2023)
Introduction: Dairy products are loved by people because of their high nutritional value, but they have also become the most ideal breeding places for microorganisms. Some dairy packaging has the problem of lax sealing, resulting in products susceptible to contamination and deterioration. The harmful microorganisms and bacteria contained in them will pose a serious threat to people’s health. Therefore, a good antibacterial protection is very important for dairy products. The purpose of this paper is to study the preparation and reverse recycling logistics of a new type of nano-filled antibacterial layer packaging film for dairy products. Methods: A new type of nano-filled antibacterial layer packaging film is prepared by extrusion casting method, and its mechanical properties and antibacterial properties are analyzed. Results: The experimental results in this article show that the prepared new nano-filled antibacterial layer packaging film has lower light transmittance and water vapor transmission rate, and has obvious antibacterial properties against Staphylococcus aureus and Escherichia coli, and has good barrier properties. Discussion: The antibacterial rate of the bacteria in the petri dish is as high as 99.97% after being placed for 120 days, and the antibacterial performance can be enhanced by the ratio of glycerol and starch content, and the new nano-filled antibacterial film prepared is degradable Sex, can be better recycled.